A simple optical tissue clearing pipeline for 3D vasculature imaging of the mediastinal organs in mice - Sun, Quanchao; Picascia, Tiziana; Khan, Arif ul Maula; Heuveline, Vincent; Gretz, Norbert (International journal of experimental pathology, 2021)
Optical tissue clearing (OTC) methods render tissue transparent by matching the refractive index within a sample to enable three-dimensional (3D) imaging with advanced microscopes. The application of OTC method in mediastinal organs in mice remains poorly understand. Our aim was to establish a simple protocol pipeline for 3D imaging of the mediastinal organs in mice. Trachea, oesophagus, thymus and heart were harvested from mice after retrograde perfusion via the abdominal aorta. We combined and optimized antibody labelling of thick tissue samples, OTC with cheap and non-toxic solvent ethyl cinnamate (ECi), and light-sheet fluorescence microscopy (LSFM) or laser confocal fluorescence microscopy (LCFM) to visualize the vasculature of those tissues. A high degree of optical transparency of trachea, oesophagus, thymus and heart was achieved after ECi-based OTC. With anti-CD31 antibody immunofluorescence labelling before ECi-based OTC, the vasculature of these tissues with their natural morphology, location and organizational network was imaged using LSFM or LCFM. This simple protocol pipeline provides an easy-to-setup and comprehensive way to study the vasculature of mediastinal organs in 3D without any special equipment. We anticipate that it will facilitate diverse applications in biomedical research of thoracic diseases and even other organs.
Gesehen am 28.11.2022